2001
DOI: 10.17705/1cais.00702
|View full text |Cite
|
Sign up to set email alerts
|

Design Science II: The Impact of Design Science on E-Commerce Research and Practice

Abstract: With the promises of e-commerce come problems and opportunities for researchers and practitioners. One of these opportunities is taking a design science approach to e-commerce research. The argument is made that design science makes a contribution of theory in business school research. Contributions of design science to the research and practice of e-commerce are categorized into artifacts that aid e-commerce practitioners, artifacts that aid ecommerce researchers, and theories related to these artifacts. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Benbasat and Zmud [9] have suggested that IS research needs to be relevant to practice, so design sciences [5,6] should be part of IS research. Their call resonated in a recent paper by Hevner et al, who argued that IS behavioral science "focuses on developing and justifying theories that explain and predict phenomena" related to IT applications, whereas design science "focuses on creating and evaluating innovative IT artifacts that enable organiDownloaded by [University of Otago] at 03:53 23 July 2015 zations to address important information-related tasks" [26, p. 98].…”
Section: Results On Perceived Diagnosticity and Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Benbasat and Zmud [9] have suggested that IS research needs to be relevant to practice, so design sciences [5,6] should be part of IS research. Their call resonated in a recent paper by Hevner et al, who argued that IS behavioral science "focuses on developing and justifying theories that explain and predict phenomena" related to IT applications, whereas design science "focuses on creating and evaluating innovative IT artifacts that enable organiDownloaded by [University of Otago] at 03:53 23 July 2015 zations to address important information-related tasks" [26, p. 98].…”
Section: Results On Perceived Diagnosticity and Flowmentioning
confidence: 99%
“…Therefore, the data from these three subjects were also discarded, leaving 80 valid responses, with 20 in each of the four treatment groups. 6 Downloaded by [University of Otago] at 03:53 23 July 2015 126 JIANG AND BENBASAT Among these 80 subjects, 53 were female and 27 male. Eleven were graduate students, and the other 69 were undergraduate students with an average of 2.74 years at the university.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed dynamic business model elements are a synthesis of the authors formulae (3), providing practical contribution for business users. It's scientific roots originate in so-called design science (Owen 1997) and its recent upsurge in Information Systems research (March, Smith 1995;Au 2001;Ball 2001;Hevner et al 2004). Fig.…”
Section: Dynamic Intellectual Capital Business Modelmentioning
confidence: 99%
“…Comparable work has been promoted in IS as "design science" through the work of March and Smith (1995), who developed a framework to demonstrate the relationship, activities, and outputs of design and natural science research in information technology. The design science ideas of March and Smith have enjoyed recent currency with a number of authors using or building on their works (Au, 2001;Ball, 2001;Hevner and March, 2003;Hevner et al, 2004).…”
Section: Constructive Research and Design Sciencementioning
confidence: 99%